Razvoj gozdnih sestojev na nekdanjih novinah v Koprivni - Golob, Janez (Acta silvae et ligni, 2019)
We conducted the sixth consecutive measurement of permanent research plots located in former slash-and-burn areas in the cadastral community of Koprivna. The forests on the research plots are privately owned and have not been subjected to significant forest management since their establishement in 1960. Natural succession, which began 70 or 100 years ago, was dominated by Norway spruce. The study shows that in untreated Norway spruce stands, the estimation of changes and the self-thinning process are comparable to Reineke%s self-thinning rule or Stand Density Index (SDI). In the research plots, the growing stock ranges from 566.4 m3/ha to 761.3 m3/ha, and basal area ranges from 48.7 m2/ha to 61.7 m2/ha. When comparing our results to previous available measurements, we observed a significant increase in forest stand height curves. In untreated stands without thinning operations, the predominant proportion of trees had a high and unfavourable height-diameter ratio (h/d).
Keywords: esearch plots; gozdovi na opuščenih kmetijskih površinah; novinarjenje; post-agricultural forests; raziskovalne ploskve; slash-and-burn cultivation; successional development; sukcesijski razvoj